PENGARUH KOMUNIKASI ORGANISASI DAN PEMBAGIAN KERJA TERHADAP EFEKTIFITAS KERJA KARYAWAN PT DAYA GUNA SEJAHTERA KABUPATEN ROKAN HILIR - Lia Veronica; Marzolina '; Sjahruddin ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study was conducted based on PT Daya Guna Sejahtera Rokan Hilir. This study aims to determine the effect simultaneously and partially Communications and Organizational Effectiveness Division of Labor Against Employees PT DayaGuna Sejahtera Rokan Hilir. Consists of three variables: the dependent variable and two independent variables. This study use regression and The study was conducted with a sample of 64 people. Research using census techniques by giving questionnaires to the respondents. In terms of data analysis, using qualitative and quantitative methods using SPSS (Statistical Package for Social Sciences) version 20.0. The leadership and management of PT Daya Guna Sejahtera Rokan Hilir in order to increase the variable and Organizational Communication Division of Labour is to create a coordinated work, provide workload in accordance with the capacity and skills of employees, willing to go straight spaciousness to directemployees directly in order to create communication organization and division of labor and increase the effectiveness of work.Keywords: Organizational Communication, Division of Labor, and Employment Effectiveness